Strategi Perubahan Perilaku Pemilihan Septic Tank di Permukiman Daerah Rendah (Studi Kasus Kota di Banjarmasin) - Juanda A. Zuraini (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Strategy of Septic Tank Choice Behavioral Change in Low Area Settlement (Case Study in Banjarmasin City). The coverage of liquid waste management service in Banjarmasin City by using septic tank through off site handling as well as in site handling according to the National Standard of Indonesia to date can serve approximately 6-7% of all residents of Banjarmasin. This means that individual use of septic tank is around 93-94% of all residents. This study was done in Banjarmasin City, South Kalimantan, including 5 districts of Central Banjarmasin, East Banjarmasin, West Banjarmasin, North Banjarmasin, and South Banjarmasin. The study was done in April 2014 until February 2016. The population for behavioral change development strategy sub system was originated from Public Health Office, Public Works Service, Drainage and Water Resource Office, Living Environment Department, Local Company of Wastewater Management, and public figures. The results showed that according to SWOT analysis, strategy of septic tank choice behavior development in Banjarmasin City settlement was in G room of quadrant IV, so the strategy used was conglomerate diversification strategy through the change of guided behavior predisposing factors to adoption phase, enabling factor of change in understanding of the availability of standardized disposal facilities, and amplifier factor needed an optimization of local regulation socialization in Banjarmasin City related to fecal disposal. Keywords: Behavioral Change; Septic Tank Choice; SWOT Analysis.